Biological Functions of Gasdermins in Cancer: From Molecular Mechanisms to Therapeutic Potential - Wang, Man; Chen, Xinzhe; Zhang, Yuan (Frontiers in Cell and Developmental Biology, 2021)
Pyroptosis is a type of lytic programmed cell death triggered by various inflammasomes that sense danger signals. Pyroptosis has recently attracted great attention owing to its contributory role in cancer. Pyroptosis plays an important role in cancer progression by inducing cancer cell death or eliciting anticancer immunity. The participation of gasdermins (GSDMs) in pyroptosis is a noteworthy recent discovery. GSDMs have emerged as a group of pore-forming proteins that serve important roles in innate immunity and are composed of GSDMA-E and Pejvakin (PJVK) in human. The N-terminal domains of GSDMs, expect PJVK, can form pores on the cell membrane and function as effector proteins of pyroptosis. Remarkably, it has been found that GSDMs are abnormally expressed in several forms of cancers. Moreover, GSDMs are involved in cancer cell growth, invasion, metastasis and chemoresistance. Additionally, increasing evidence has indicated an association between GSDMs and clinicopathological features in cancer patients. These findings suggest the feasibility of using GSDMs as prospective biomarkers for cancer diagnosis, therapeutic intervention and prognosis. Here, we review the progress in unveiling the characteristics and biological functions of GSDMs. We also focus on the implication and molecular mechanisms of GSDMs in cancer pathogenesis. Investigating the relationship between GSDMs and cancer biology could assist us to explore new therapeutic avenues for cancer prevention and treatment.